Broadband Access Communication Technologies XIV 2020
DOI: 10.1117/12.2543983
|View full text |Cite
|
Sign up to set email alerts
|

3.8-Gbit/s visible light communication (VLC) based on 443-nm superluminescent diode and bit-loading discrete-multiple-tone (DMT) modulation scheme

Abstract: s visible light communication (VLC) based on 443-nm superluminescent diode and bitloading discrete-multiple-tone (DMT) modulation scheme,"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Notable research efforts have explored the use of low-coherence light sources for data transmission across various scenarios 61,191,192 . In 2016, Shen et al, investigated for the first time the implementation of low coherent light using semipolar GaN SLDs in communication systems 61 .…”
Section: Optical Communication and Illuminationmentioning
confidence: 99%
“…Notable research efforts have explored the use of low-coherence light sources for data transmission across various scenarios 61,191,192 . In 2016, Shen et al, investigated for the first time the implementation of low coherent light using semipolar GaN SLDs in communication systems 61 .…”
Section: Optical Communication and Illuminationmentioning
confidence: 99%
“…In addition, light has other advantages over radio, namely being free of radiation and free of electromagnetic interference. Hu et al [165] uses 443-nm GaN-based superluminescent diode (SLD), discretemultiple-tone (DMT) modulation, and 256-QAM technology and gets speeds of up to 3.8 Gbit/s. These results make VLC technology more effective for smart lighting.…”
Section: ) Led Development In Color and Brightnessmentioning
confidence: 99%
“…Since developing high-power and high-speed violet-blue SLDs, VLC systems based on SLD transmitters have been demonstrated with data rates of 3.8 Gbps with a DMT modulation scheme by Hu, F. et al in 2020 [75]. Studies have shown that GaN-based SLDs can achieve high power emission power, such as over 100 mW blue SLD in continuous wave operation [76].…”
Section: Super Luminescent Diodes (Slds)mentioning
confidence: 99%